2011
DOI: 10.1007/978-3-642-19260-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Internet Censorship in China: Where Does the Filtering Occur?

Abstract: Abstract. China filters Internet traffic in and out of the country. In order to circumvent the firewall, it is helpful to know where the filtering occurs. In this work, we explore the AS-level topology of China's network, and probe the firewall to find the locations of filtering devices. We find that even though most filtering occurs in border ASes, choke points also exist in many provincial networks. The result suggests that two major ISPs in China have different approaches placing filtering devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 2 publications
4
67
0
Order By: Relevance
“…They also proposed ConceptDoppler, a system for monitoring which keywords are filtered over time. In more recent work on censorship in China [76], Xueyang Xu et al explored the AS-level topology of China's network and probed the firewall to find the locations of filtering devices. They found that two major ISPs in China had different approaches to the placement of filtering devices, either decentralized or in the backbone.…”
Section: Related Workmentioning
confidence: 99%
“…They also proposed ConceptDoppler, a system for monitoring which keywords are filtered over time. In more recent work on censorship in China [76], Xueyang Xu et al explored the AS-level topology of China's network and probed the firewall to find the locations of filtering devices. They found that two major ISPs in China had different approaches to the placement of filtering devices, either decentralized or in the backbone.…”
Section: Related Workmentioning
confidence: 99%
“…China has received the most attention [4,18,47,67,70]. Similar studies have been published for Iran [6], Pakistan [44,45], and Turkey [45].…”
Section: Previous Workmentioning
confidence: 82%
“…They also proposed ConceptDoppler, a system for monitoring which keywords are filtered over time. In more recent work on censorship in China [64], Xueyang Xu et al explored the AS-level topology of China's network and probed the firewall to find the locations of filtering devices. They found that two major ISPs in China had different approaches to the placement of filtering devices, either decentralized or in the backbone.…”
Section: Related Workmentioning
confidence: 99%